2013
DOI: 10.1039/c3ra42528b
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the structure and optical properties of copper sulfide thin films chemically deposited on various substrates

Abstract: Copper sulfide (Cu x S) thin films were chemically deposited from solution onto glass, Si(100) and GaAs(100) substrates. The microstructure and morphology evolution were investigated using X-ray diffraction, scanning electron microscopy and transmission electron microscopy. As-deposited films were found to be amorphous or semi-crystalline, while X-ray diffraction and selected area electron diffraction measurements indicated that the annealed films were composed of a mixture of Covellite (CuS) and Digenite (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 47 publications
1
30
0
Order By: Relevance
“…The sharp band at 468 cm -1 is attributed to S-S stretching vibration, while a weak band at 263 cm -1 corresponds to A 1g TO mode. Both of these peaks have been associated with the covellite phase of CuS (Munce et al 2007;Safrani et al 2013).…”
Section: Raman Spectroscopic Studymentioning
confidence: 99%
“…The sharp band at 468 cm -1 is attributed to S-S stretching vibration, while a weak band at 263 cm -1 corresponds to A 1g TO mode. Both of these peaks have been associated with the covellite phase of CuS (Munce et al 2007;Safrani et al 2013).…”
Section: Raman Spectroscopic Studymentioning
confidence: 99%
“…In the 1950s, the discovery of the photovoltaic effect in CdS−CuS heterojunction brought a great attention to CuS, but its structural instability reduced the expectations for this mineral . With the advent of the nanoscience and improvements in the shape and size controlling of micro/nanostructures synthesis enhancing their physical‐chemical properties called again the attention of the researchers .…”
Section: Introductionmentioning
confidence: 99%
“…The intensity change in (200) peak, as shown in the inserted pattern, highlights the strong dependency of crystallization on the content of Cu. It has been reported that Cu in the chemical bath deposition may have different reaction kinetics in forming the chalcogenide phase so that the involvement of Cu precursor acts negatively in the sulfide formation[23][24][25].…”
mentioning
confidence: 99%